Effects of Migration on Perceived Health Status in Brazil’s Southeast and Midwest Regions - Raquel Andréia Rieger; Laís de Sousa Abreu Soares; Evandro Camargos Teixeira; Franscisco Carlos da Cunha Cassuce (Lecturas de Economía)
The present article aims to analyze the effects of migration on the health status reported by individuals who migrated to Brazil’s Midwest and Southeast regions. It also aims to ascertain the significance of a migrant's origin in determining the health status reported and whether the years of residence in the region of destination affect this status. The Pseudo-Panel technique is applied by means of a Pooled Ordered Probit model, with the self-declared health status of individuals as the dependent variable. Data were obtained from the National Household Sample Survey (PNAD) for the years 1998, 2003 and 2008. The results show that migrants residing in the Southeast tended to declare a health status that was inferior to that of native-born residents, whereas no statistical significance was observed in the Midwest.